The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/v14030547
|View full text |Cite
|
Sign up to set email alerts
|

A Tug of War: Pseudorabies Virus and Host Antiviral Innate Immunity

Abstract: The non-specific innate immunity can initiate host antiviral innate immune responses within minutes to hours after the invasion of pathogenic microorganisms. Therefore, the natural immune response is the first line of defense for the host to resist the invaders, including viruses, bacteria, fungi. Host pattern recognition receptors (PRRs) in the infected cells or bystander cells recognize pathogen-associated molecular patterns (PAMPs) of invading pathogens and initiate a series of signal cascades, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 157 publications
1
17
0
Order By: Relevance
“…m 6 A modification was involved in regulating the host immune response to various viral infections (Mcfadden and Horner, 2021), and many viruses utilized m 6 A modification to evade host innate immunity (Kim et al, 2020;Lu et al, 2020Lu et al, , 2021Xue et al, 2021). PRV had evolved a variety of host immune escape mechanisms (Ye et al, 2022), so m 6 A modification might be involved in regulating host immune escape after PRV infection. KEGG analysis showed that the water reabsorption pathway was the first pathway involved by hypomethylated genes, which might be due to the selection of kidney cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A modification was involved in regulating the host immune response to various viral infections (Mcfadden and Horner, 2021), and many viruses utilized m 6 A modification to evade host innate immunity (Kim et al, 2020;Lu et al, 2020Lu et al, , 2021Xue et al, 2021). PRV had evolved a variety of host immune escape mechanisms (Ye et al, 2022), so m 6 A modification might be involved in regulating host immune escape after PRV infection. KEGG analysis showed that the water reabsorption pathway was the first pathway involved by hypomethylated genes, which might be due to the selection of kidney cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-I-mediated innate immune response is one of the most effective defense strategies of the host against viral infection. However, viruses have developed various strategies to evade host immunity during their long evolution (Garcia-Sastre, 2017;O'Connor and Sen, 2021;Verzosa et al, 2021;Ye et al, 2022). PRV regulates the host innate immune responses in several strategies.…”
Section: Ifn-i Systemmentioning
confidence: 99%
“…Subsequently, the adaptive immune response is elicited to facilitate the clearance of pathogens and the generation of immunological memory [ 28 ]. Meanwhile, pathogens have also developed multiple mechanisms to escape the host immune response [ 29 ]. Thus, the war between virus and host always continues.…”
Section: Introductionmentioning
confidence: 99%